1994
DOI: 10.1038/ki.1994.451
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-mediated regulation of renin secretion

Abstract: The aim of the present study was to investigate the endothelial influence on renin secretion of isolated juxtaglomerular cells. Specifically the role of nitric oxide (NO) and of endothelin was studied. Coculture of primary cultures of juxtaglomerular cells with aortic and microvascular endothelial cells decreased renin secretion. Inhibition of NO formation by absence of l-arginine or presence of N omega-nitro-l-arginine caused a marked decrease in cGMP accumulation and a reduction in renin secretion in cocultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…In vitro, however, in renal cortical slices, L-NMMA increases [117,118] and NO decreases [110] renin secretion. This is perhaps partly explained by the biphasic effect of NO on renin secretion: a short-term inhibition and a long-term stimulation [116]. Conversely, in isolated juxtaglomerular cells renin secretion is increased by NO and decreased by NOS inhibitors.…”
Section: No and Reninmentioning
confidence: 78%
See 1 more Smart Citation
“…In vitro, however, in renal cortical slices, L-NMMA increases [117,118] and NO decreases [110] renin secretion. This is perhaps partly explained by the biphasic effect of NO on renin secretion: a short-term inhibition and a long-term stimulation [116]. Conversely, in isolated juxtaglomerular cells renin secretion is increased by NO and decreased by NOS inhibitors.…”
Section: No and Reninmentioning
confidence: 78%
“…Furthermore NO inhibition attenuates the renin response to a low-salt diet [109] and pressure-dependent renin release [112], suggesting a necessity for NO to be present for the normal renin response to salt depletion and low blood pressure. In studies using cultured juxta glomerular cells, NO appears to stimulate renin release [113][114][115] and this is dependent on extracellular Ca 2+ [116]. In vitro, however, in renal cortical slices, L-NMMA increases [117,118] and NO decreases [110] renin secretion.…”
Section: No and Reninmentioning
confidence: 85%
“…Specifically, the expression of eNOS in the afferent arteriole has been shown for a number of mammalian species (40, 41, 896). A coculture of JG cells with endothelial cells revealed both inhibitory and stimulatory signaling derived from the endothelial cells, with the stimulatory component related to endothelium-dependent NO formation (462,481,773). In contrast, the NOS inhibition in the absence of endothelial cells had no effect on the renin secretion from JG cells, presumably due to the lack of NOS expression in JG cells (773).…”
Section: Nomentioning
confidence: 96%
“…Additionally, some studies report that NOx lowers plasma renin levels; however, other studies have shown that NOx increases renin levels. 35,36 Although the mechanism of this impairment is not well understood, a number of studies have shown that the eNOS pathway and/or the released NOx are influenced by oxLDL. 37 As previous results are controversial, further studies are needed to determine the cellular and molecular mechanisms by which NOx regulates various precursors to HT.…”
Section: Discussionmentioning
confidence: 99%